Door of the Wilderness: The Greek, Coptic, and Copto-Arabic Sayings of St. Antony of Egypt : An English Translation, with Introductions and Notes - Agaiby, Elizabeth, (Texts and Studies in Eastern Christianity ;, 2022)
Saint Antony of Egypt (c. 251-356), often called "the father of monasticism," has numerous representations: the Antony of the Life of Antony and the Letters , but also the Antony of around 120 sayings or apophthegmata. This volume presents fresh English translations of the Greek and Coptic sayings, as well as the first English translation of the Copto-Arabic sayings that are based on unpublished manuscripts. The volume thus opens the door to a richer image of Saint Antony's many identities across various languages and traditions.